Cephalexin Levels in Human Bile in Presence of Biliary Tract Disease. Issue 5824 (19th August 1972) - Sales, J. E. L.; Sutcliffe, Marion; O'Grady, F.
Abstract : Cephalexin was given to 24 patients before and after operation on the bile ducts and gall bladder. Two patients had obstructive jaundice. Samples of the bile were taken either directly from the gall bladder at operation or via the T-tube. Cephalexin was excreted in the bile, peak levels being obtained after two to three hours. These levels could be raised if probenecid was given concurrently. Higher levels were found in patients with functioning gall-bladders. A trial of cephalexin seems justified for the treatment of typhoid carriers.